The Effects of Different Intensive Physical Performances by athletes on Selected Hematological Parameters - Shumoos H Alwaid (Institute of Medico-legal Publications Pvt Ltd, 2021)
The aim of this review study is to compare the effects of different intensive physical performances andcompetitions from several studies include (football, basketball, 24h marathon race and cycling) games onhematological parameters of males players. And to find the one with strongest effect on those parametersamong the performances. The Hematological parameter include white blood cell count (WBC ) , redblood cell count (RBC) count , hemoglobin (HGB), haematocrit (HCT), mean cell volume (MCV) , meancorpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and platelet count(PLT). Iron and Feritten level also estimated in one study. When comparing the blood values for all theplayers before and after the competitions period, there were significant differences in prevalence of most ofblood parameters in all studies but the most impact was in 24 h marathon performance of 11 male runnerswho raced for 24 hours around a 400 m oval track, covering at least 100 km of distance. The runners changedcourse every 4 hours and were allowed to rest and freely consume food and water. The blood samples wereobtained from subject in 2 and 9 days prior to competition and after competition. The result was showing thatthe the runners suffering from distinguish blood anemia appear after competition in 2 day. The findings showthat the hematological parameters could be affected by endurance of performance depending on competitiontime period and intensity of physical performance.